Non-linear ultrasonic test for fiber-reinforced concrete using 3rd harmonic generation - Ongpeng, Jason Maximino C. (Animo Repository, 2015)
This paper presents non-linear ultrasonic behavior observed in ultrasonic transmission test for fiber- reinforced concrete cubes l5Omm x l5Omm x l5Omm with three water-cement ratios 40%, 50% and 6O%. The fibers used were short steel fibers having l% volumetric ratio. Modes of failure were documented using pictures to relate the behavior of the 3rd harmonic amplitude as load patterns were varied. The normalized 3rd harmonic generation were generated thru Fast Fourier Transform FFT frequency spectra and normalizing it at fundamental frequency of lOOkHz. The difference (3rd harmonic dB difference) from each varying step load for the 3rrd harmonic amplitude and baseline of zero load's 3rd harmonic amplitude were analyzed. Categorization of modes of failure was done to generalize the behavior of 3rd harmonic dB difference according to the step load pattern. The satisfactory mode of failure produced similar pattern with respect to the step load variation. The 3rd harmonic dB difference increases as load increases, and decreases when the load decreases.